Risk factors associated with medial tibial stress syndrome in runners: a systematic review and meta-analysis - Newman P; Witchalls J; Waddington G; Adams R (Dove Medical Press, 2013)
Phil Newman, Jeremy Witchalls, Gordon Waddington, Roger Adams Faculty of Health, Physiotherapy, University of Canberra, Bruce, ACT, Australia Background: Medial tibial stress syndrome (MTSS) affects 5%–35% of runners. Research over the last 40 years investigating a range of interventions has not established any clearly effective management for MTSS that is better than prolonged rest. At the present time, understanding of the risk factors and potential causative factors for MTSS is inconclusive. The purpose of this review is to evaluate studies that have investigated various risk factors and their association with the development of MTSS in runners. Methods: Medical research databases were searched for relevant literature, using the terms “MTSS AND prevention OR risk OR prediction OR incidence”. Results: A systematic review of the literature identified ten papers suitable for inclusion in a meta-analysis. Measures with sufficient data for meta-analysis included dichotomous and continuous variables of body mass index (BMI), ankle dorsiflexion range of motion, navicular drop, orthotic use, foot type, previous history of MTSS, female gender, hip range of motion, and years of running experience. The following factors were found to have a statistically significant association with MTSS: increased hip external rotation in males (standard mean difference [SMD] 0.67, 95% confidence interval [CI] 0.29–1.04, P<0.001); prior use of orthotics (risk ratio [RR] 2.31, 95% CI 1.56–3.43, P<0.001); fewer years of running experience (SMD –0.74, 95% CI -1.26 to –0.23, P=0.005); female gender (RR 1.71, 95% CI 1.15–2.54, P=0.008); previous history of MTSS (RR 3.74, 95% CI 1.17–11.91, P=0.03); increased body mass index (SMD 0.24, 95% CI 0.08–0.41, P=0.003); navicular drop (SMD 0.26, 95% CI 0.02–0.50, P=0.03); and navicular drop >10 mm (RR 1.99, 95% CI 1.00–3.96, P=0.05). Conclusion: Female gender, previous history of MTSS, fewer years of running experience, orthotic use, increased body mass index, increased navicular drop, and increased external rotation hip range of motion in males are all significantly associated with an increased risk of developing MTSS. Future studies should analyze males and females separately because risk factors vary by gender. A continuum model of the development of MTSS that links the identified risk factors and known processes is proposed. These data can inform both screening and countermeasures for the prevention of MTSS in runners. Keywords: medial tibial stress syndrome, injury prevention, risk factors, running injuries